2018
DOI: 10.1126/science.aao6575
|View full text |Cite
|
Sign up to set email alerts
|

A LIMA1 variant promotes low plasma LDL cholesterol and decreases intestinal cholesterol absorption

Abstract: A high concentration of low-density lipoprotein cholesterol (LDL-C) is a major risk factor for cardiovascular disease. Although LDL-C levels vary among humans and are heritable, the genetic factors affecting LDL-C are not fully characterized. We identified a rare frameshift variant in the (also known as or ) gene from a Chinese family of Kazakh ethnicity with inherited low LDL-C and reduced cholesterol absorption. In a mouse model, LIMA1 was mainly expressed in the small intestine and localized on the brush bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 45 publications
4
83
0
Order By: Relevance
“…Fecal triglyceride, serum triglyceride, and free fatty acid measurements Fecal triglyceride was measured as described previously [40]. Briefly, feces were collected, freeze-dried, and ground to powder.…”
Section: Metabolic Parameter Measurementsmentioning
confidence: 99%
“…Fecal triglyceride, serum triglyceride, and free fatty acid measurements Fecal triglyceride was measured as described previously [40]. Briefly, feces were collected, freeze-dried, and ground to powder.…”
Section: Metabolic Parameter Measurementsmentioning
confidence: 99%
“…GWAS has been performed extensively on blood lipids traits and more than 300 risk loci were found in different populations 5 . These loci cover almost all the well-known genes that are important in lipid metabolism, such as LDLR 6 , ARH 7 , ABCA1 8 , ABCG5/G8 9 , PCSK9 10 , NPC1L1 11,12 , LIMA1 13 , et al Although GWAS is a powerful approach, we find that about 2/3 of these risk loci are located in noncoding regions and are not close to any gene known plays a role in lipid metabolism. The disease-causing variants in these loci and their underlying molecular mechanism remain largely unknown, which prevent the interpretation of the GWAS results and their application in precise medicine.…”
Section: Figure 1mentioning
confidence: 73%
“…The rs58542926 polymorphic variant of the TM6SF2 gene is used to identify individuals with a higher susceptibility to chronic liver diseases, especially hepatocellular carcinoma, cirrhosis, alcoholic liver disease, and nonalcoholic fatty liver disease [121,122]. LIMA1 encodes a negative regulator of cholesterol absorption, and its mutations lead to a decrease in the LIMA1 protein level [123]. In studies on mice and humans, LIMA1 has been identified as a key protein regulating intestinal cholesterol absorption [124].…”
Section: Discussionmentioning
confidence: 99%